Dawn of fear ebook - Cooper, Susan (2023)
Young boys grapple with daily life in London during World War II in this historical novel by the Newbery Honor–winning author of The Dark Is Rising . The circumstances may sound extraordinary, but for Derek and his friends, who are living outside of London during World War II, air raids are a normal part of everyday lie. When a particularly violent raid closes their school for a few days, the boys are happy to use the time to complete the construction of their secret camp. But to their horror, their refuge is savagely attacked by a rival neighborhood gang. Derek and his friends carry out a daring plan to ambush the enemy gang, which leaves Derek feeling unsettled and—for the first time—fearful of the war around him. And then, after one night filled with bombing, the war changes his world forever. Praise for Dawn of Fear An ALA Notable Children's Book "Remarkable . . . A moving chronicle of despair and of courage." — Publishers Weekly "An uncommon kind of war story." — The Horn Book "Well-written . . . [Doesn't] shy from realistic facts and emotions." — The New York Times "A cracking good read." —Historical Novel Society Reader Chat Page Inside